Digital Skills Workshop for Adult: Mastering the Basics of Technology in the Digital Age - Hera Khairunnisa; Zairin, Gentiga Muhammad; Saparuddin Mukhtar; Wahono, Puji; Muhammad Edo Suryawan Siregar; Shandy Aditya; Anisa Putri Isnaini; Dwi Handarini; Charlie Albert Lasuin (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
This program aimed to enhance digital awareness and literacy by equipping participants with essential knowledge and skills in navigating the digital environment. The webinar, held on July 15, 2024, attracted 80 participants, including students, lecturers, and the general public from Jakarta State University and Universiti Malaysia Sabah. Expert speakers addressed critical topics such as maintaining human connection in the digital age (Charlie Albert Lasuin, Universiti Malaysia Sabah), responsible data collection for economists (Prof. Dr. Puji Wahono, S.E., M.Sc., Jakarta State University), and the interplay between social media and data privacy (Shandy Aditya, Jakarta State University). The program successfully engaged participants, sparking active discussion and a desire for further learning in digital and social literacy.